A Metropolitan History of the Dutch Empire : Popular Imperialism in the Netherlands, 1850-1940. - Kuipers, Matthijs (Heritage and memory studies., 2022)
This book analyses popular imperial culture in the Netherlands around the turn of the twentieth century. Despite the prominent role that the Dutch empire played in many (sometimes unexpected) aspects of civil society, and its significance in mobilising citizens to participate in causes both directly and indirectly related to the overseas colonies, most people seem to have remained indifferent towards imperial affairs. How, then, barring a few jingoist outbursts during the Aceh and Boer Wars, could the empire be simultaneously present and absent in metropolitan life? Drawing upon the works of scholars from fields as diverse as postcolonial studies and Habsburg imperialism, 'A Metropolitan History of the Dutch Empire' argues that indifference was not an anomaly in the face of an all-permeating imperial culture, but rather the logical consequence of an imperial ideology that treated?the metropole? and?the colony? as entirely separate entities. The various groups and individuals who advocated for imperial or anti-imperial causes? such as missionaries, former colonials, Indonesian students, and boy scouts? had little unmediated contact with one another, and maintained their own distinctive modes of expression. They were all, however, part of what this book terms a?fragmented empire?, connected by a Dutch imperial ideology that was common to all of them, and whose central tenet? namely, that the colonies had no bearing on the mother country? they never questioned. What we should not do, the author concludes, is assume that the metropolitan invisibility of colonial culture rendered it powerless.